Population structure of Toxoplasma gondii in Argentina - Bernstein, Mariana (2018)
The protozoan Toxoplasma gondii is worldwide distributed showing a particular population structure that may differ among continents and countries. The aim of this study was to analyze the T. gondii population structure in Argentina and compare it with genotyping information from other South American countries. For the analysis, 39 samples from Argentina (isolates from the provinces of Buenos Aires, Misiones, Entre Ríos and San Luis) were genotyped using 10 multilocus PCR-RFLP markers including SAG1, SAG2 (5′-3′SAG2, alt. SAG2), SAG3, BTUB, GRA6, C22-8, C29-2, L358, PK1, and Apico. The T. gondii DNA samples were obtained from domestics animals (chickens n = 20; cats n = 3; pigs n = 2; goat n = 1; rabbit n = 1), humans (n = 6), zoo animals (n = 5) and a rat (n = 1). Phylogenetic relationship of these Argentinean isolates together with representative reference genotypes was determined by phylogenetic network analysis. Thirty-seven Argentinean samples belonged to 21 genotypes and two samples were genotyped at 8 of the 10 loci and considered incomplete characterized. Among these 37 typed samples, five genotypes were not previously reported. The majority of the samples grouped with the Type III (ToxoDB PCR-RFLP genotype #2) lineage. The clonal Type II (ToxoDB genotypes #1 and #3) was also identified. Our results suggest a unique population structure with combination of unique genotypes and the common Type II and Type III lineages in Argentina. Nevertheless, different regions showed distinctive pattern of genotypes, revealing a higher variability in Northern provinces.